The Quality Changed of Dairy Cow’s Milk Adulterated by Water: In Chemical Milk Studies - Syamsi, Afduha Nurus; Subagyo, Yusuf; Safitri, Lis (Universitas Halu Oleo, 2023)
The study aimed to obtain a comprehensive description of the chemical quality decrease of milk adulterated with water from different sources. Experimental research was carried out at the Dairy Production Laboratory, with the main material being milk from the Experimental Farm, Faculty of Animal Science, Unsoed. The study used a completely randomized design (CRD)-factorial. Factor A was three types of milk (no adulterated milk (NA), adulterated by farm water (AFW), and adulterated by house water (AHW)). Factor B was six times of storage (0; 4; 8; 12; 16; 20 hours). There were 18 treatments, each repeated three times. Thus, there were 54 units. Milk quality was observed at controlled room temperature, namely the average temperature of Purwokerto City (300C) in the incubator. Data were analyzed for variance and further tested for linear regression. The analysis of variance showed that the interaction between the type of adulteration and storage time had a very significant effect (P